Caracteres geomorfológicos de la Depresión de Valdecebro (provincia de Teruel) - Sánchez Fabre, Miguel (Geographicalia, 2017)
In this article we analyse the geornorphology in the area of the Valdecebro Depression (Teruel). We especially study the modelling of the several levels of glacis which show the different phases of the Depression evolution for the last Pliocene-Quaternary Period.